Perception of a sample of mathematics teachers on training received in the university - Chaves Esquivel, Edwin (2013)
The main objective of this study was to determine the perception of a sample of 249 mathematics teachers regarding the training received in their university. We identified strengths and weaknesses of the academic programs that train teachers of mathematics in the country, according to the teachers. The sample included educators trained in public and private universities, working at different educational regions of the country. The information was gathered through a questionnaire. Overall, educators perceive training in theoretical mathematics as the main strength. However, according to the scale used, all other aspects related to the formation process of a math teacher had a low perception. Within the mentioned weaknesses are: training in educational elements, evaluative, methodological, philosophical, psychological and historical, as well as the lack of adequate preparation in the use of technological resources in teaching. These opinions are a valuable input to the universities, because they show the opinions held by graduates of the training received.